SWSex Stars, Old Novae, and the Evolution of Cataclysmic Variables - L. Schmidtobreick; C. Tappert (Acta Polytechnica CTU Proceedings)
The population of cataclysmic variables with orbital periods right above the period gap are dominated by systems with extremely high mass transfer rates, the so-called SW Sextantis stars. On the other hand, some old novae in this period range which are expected to show high mass transfer rate instead show photometric and/or spectroscopic resemblance to low mass transfer systems like dwarf novae. We discuss them as candidates for so-called hibernating systems, CVs that changed their mass transfer behaviour due to a previously experienced nova outburst. This paper is designed to provide input for further research and discussion as the results as such are still very preliminary.